Bridging language and nursing proficiency: Technology-enhanced TBLT integrated into CLIL in ESP instruction - Dodi Mulyadi; Testiana Deni Wijayatiningsih; Titi Hartiti; Charanjit Kaur Swaran Singh (Universitas Syiah Kuala, 2025)
The research examined the perspectives of ESP learners and lecturers regarding the implementation of technology-enhanced task-based language teaching (TBLT) integrated into content language integrated learning (CLIL) in ESP instruction, and it identified key factors affecting its effective integration. A qualitative research design was employed, involving 95 nursing students and 10 ESP lecturers, who completed an open-ended questionnaire. Moreover, participants took part in focus group discussions (FGDs), including ESP students, heads of the nursing program, ESP lecturers, nursing lecturers, stakeholders, and professional nurses. Thematic data analysis of the open-ended questionnaire and FGDs results revealed that students and lecturers viewed the implementation of technology-enhanced TBLT integrated into CLIL as beneficial for integrating nursing theory with English language proficiency, thereby significantly improving content knowledge and language competence. Nonetheless, substantial obstacles arose, encompassing technology limitations, insufficient instructor preparation, and limited interdisciplinary collaboration. The results indicate that successful implementation necessitates a robust technology infrastructure, continuous professional development for educators, and enhanced collaboration between language teachers and nursing departments. The results of this study also show that technology-enhanced TBLT integrated into CLIL can relate theoretical lessons to real-world applications. These results create a complete learning environment that gives nursing students the skills they need to meet the high standards of the medical field.